Children's aesthetic experience and the relationship work of art in artistic spaces (Olhar de Professor, 2021)
The present text aims to present a reflection on aesthetic experience in early childhood education, through the act of mining and analyzing the pedagogical documentation, which in turn carries the minutiae and evidence of children's aesthetic experiences, which are the results of an educational project of Occupation of public and cultural artistic spaces by young children between 4 and 6 years old in the city of Piracicaba. The children participating in this project collaborated in the development of the master's research in which the present article is exposed. The discussion of the right to the city and occupation permeates the idea that aesthetic formation is part of the integral formation of young children. Walter Benjamin and Lev Vigotski were considered as theoretical contributions to support the conceptual construction of children's aesthetic experience.
Keywords: Research. Child education. Occupation. City. Art.